47th AIAA Aerospace Sciences Meeting Including the New Horizons Forum and Aerospace Exposition 2009
DOI: 10.2514/6.2009-1337
|View full text |Cite
|
Sign up to set email alerts
|

A High Order Cut-Cell Method for Numerical Simulation of Hypersonic-Boundary Transition with Arbitrary Surface Roughness

Abstract: Hypersonic boundary-layer transition can be affected significantly by surface roughness. Many important mechanisms which involve transition induced by arbitrary roughness are not well understood. In this paper, we propose a new high-order cut cell method which combined the non-uniform finite difference method for discrete points near the curvilinear boundary and shock-fitting method for the bow shock. The receptivity process induced by interaction of Mach 5.92 flow over flat plate under the combination effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Since 2009, for the purpose of simulating hypersonic flow with finite height roughness elements, Duan et al has developed a highorder cut-cell method [14]. The new method was then applied to simulating finite roughness elements in a hypersonic boundary layer at Mach 5.92 [7,14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since 2009, for the purpose of simulating hypersonic flow with finite height roughness elements, Duan et al has developed a highorder cut-cell method [14]. The new method was then applied to simulating finite roughness elements in a hypersonic boundary layer at Mach 5.92 [7,14].…”
Section: Introductionmentioning
confidence: 99%
“…The new method was then applied to simulating finite roughness elements in a hypersonic boundary layer at Mach 5.92 [7,14]. Different from the wavy wall idea, as in [5] and [10], they found that the relative location of the 2-D roughness element and the synchronization location plays an important role [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since 2009, for the purpose of simulating hypersonic flow with finite height roughness element, Zhong's group at UCLA has developed a high-order cut-cell method [23]. The new method was then applied to simulating a finite roughness elements on a hypersonic boundary layer at Mach 5.92 [16,23].…”
Section: Introductionmentioning
confidence: 99%
“…It is natural that influence of roughness on the convective instability of mode S need to be examined first to investigate the cause of delaying transition. Duan et al 4,5 and Fong et al 6 investigated roughness effect on instability of mode S by using direct numerical simulations (DNS). Their DNS studies showed that the roughness located at the downstream of synchronization point can stabilize mode S. Although they imposed mode S at the inflow boundary and focused on its downstream evolution, it is possible in DNS study that the other mechanisms other than the convective instability of mode S can be involved due to roughness.…”
Section: Introductionmentioning
confidence: 99%